The Influence of Emotional Intelligence on Nurse Loyalty at RS. Sukmul Sisma Medika, North Jakarta - Ishak, Muhammad; Indrawati, Ratna; Anindita, Rina (Formosa Journal of Science and Technology, 2024)
Sukmul Sisma Medika Hospital is a private hospital and is a Class C hospital located in the Jakarta City area. The results of nurses' performance achievements over the last two years show that performance achievements have not met management targets. Regarding the problem of nurse loyalty at the Sukmul Sisma Medika Hospital, nurses were found to be nurses who did not prioritize patient satisfaction. This study aims to analyze the influence of emotional intelligence and organizational commitment on nurse loyalty with motivation as an intervening variable in hospitals. Sukmul Sisma Medika, North Jakarta. This research uses a quantitative analysis method with a cross sectional research design, the analysis tool used is SEM PLS. The sample calculation using purposive sampling was 86. The variables in this research were emotional intelligence, organizational commitment, nurse loyalty and motivation. The research uses a questionnaire as a research instrument with a 5-level Likert scale measurement. Data analyzed using the SEM PLS data processing application shows that there is a direct and indirect influence of emotional intelligence and organizational commitment on nurse loyalty with motivation as an intervening variable in hospitals. Sukmul Sisma Medika, North Jakarta.